Study of radiocesium contamination from Chernobyl accident in samples of black blueberry jams - Chiara Cantaluppi; Daniele Zannoni; Massimo Calabrese (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2021)
More than 30 years after the Chernobyl accident, foodstuff based on black blueberries (Vaccinium myrtillus) with relevant 137Cs activity concentrations are still found in the European Union market. Recently, mass media reported that food products based on black blueberries produced in UE were rejected by Asian markets because the 137Cs activity concentration was greater than 100 Bq kg-1. It is known that Ukraine, Belarus and Russia are great exporters of black blueberries: there is a strong suspicion that the berries are collected also from the most radio-contaminated areas of these countries and introduced in UE markets.  For this reason, about 40 samples of black blueberry preserves as jams, marmalades, stewed fruits were analysed with high resolution gamma spectrometry to measure 137Cs and 134Cs activity concentration. All the food preparations of the study have been collected in supermarkets and in local stores of northern Italy.  134Cs was less than minimum detectable activity in all samples, as expected following its half-life. On the other hand, 137Cs activity concentration was widely variable among samples: the minimum, mean and maximum concentration were 1, 54 and 162 Bq kg-1, respectively. The activity concentrations found in these products were corrected for the radioactive decay and reported to the same date. The activity concentration in fruits used for preserves was calculated from fruit percentage content reported on the product label. In fruits used for marmalades, jams and stewed fruits, 137Cs activity concentration up to 230 Bq kg-1 was found. In a sample of blueberries in syrup, 137Cs activity concentration in blueberries was 450 Bq kg-1. From statistical analysis and contamination data of European soil, it is clearly seen that the contamination from Chernobyl accident is still relevant in some forest ecosystems and its transfer to some vegetables must be taken in account. Organic and non-organic jams show no significant difference in terms of mean 137Cs concentration. However, a potential multimodal distribution is observed for organic products, highlighting the possibility of fruit harvesting in areas with different 137Cs soil concentration. The results of this study are aimed to expand the current knowledge on the distribution of 137Cs in black blueberry products, allowing health organizations to improve the absorbed dose budget from raw berries-based food.